Comparing Indonesia and Malaysia Public Budgeting Process - Yuhertiana, Indrawati; Suhartini, Dwi; Tannar, Oryza (Future Science, 2020)
This research is exploratory research that aims to understand the government budgeting process. Reforms to manage government for a better, more professional, and modern way has been initiated by the concept of new public management. Therefore, it is important to know the process of this change taking place. One of the outcome changes which is the concern of this research is the transparency of financial information that is conveyed to the public. Therefore, observations were made on the official government website. This study focuses on observing the process of change that occurred in the two countries of Indonesia and Malaysia. The research was conducted by combining literature studies and website studies, with the content analysis method. The study found that the budgeting process is different due to different budgeting systems. However, it has similarities in the stages used, starting from planning, budgeting, implementation, and monitoring evaluation.